2018
DOI: 10.1002/hyp.11461
|View full text |Cite
|
Sign up to set email alerts
|

Insights into agricultural influences and weathering processes from major ion patterns

Abstract: Karst areas and their catchments pose a great challenge for protection because fast conduit flow results in low natural attenuation of anthropogenic contaminants. Studies of the hydrochemistry of karst sources and river solutes are an important tool for securing and managing water resources. A study of the geochemical downriver evolution of the Wiesent River and its tributaries, located in a typical karst terrain, revealed unexpected downstream decreases of nitrate with maximum mean values of 30 mg/L at the so… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
7
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 78 publications
(103 reference statements)
1
7
0
Order By: Relevance
“…However, in this study, the ratio of Na + /Cl − is much greater than 1, indicating that the excess Na + comes from the weathering of silicates due to the ion exchange process. The results are similar to studies in Kanding, southeastern China [63], the Yellow River source region, the northeastern Qinghai-Tibetan Plateau [56], and the results are different from studies in southern Germany [62], India [66] and China [67]. NH 4 -N was detected at each sampling point in different sampling periods, which reflected the influences of human activities.…”
Section: Sources and Influencing Factors For The Major Ions And Potensupporting
confidence: 65%
See 1 more Smart Citation
“…However, in this study, the ratio of Na + /Cl − is much greater than 1, indicating that the excess Na + comes from the weathering of silicates due to the ion exchange process. The results are similar to studies in Kanding, southeastern China [63], the Yellow River source region, the northeastern Qinghai-Tibetan Plateau [56], and the results are different from studies in southern Germany [62], India [66] and China [67]. NH 4 -N was detected at each sampling point in different sampling periods, which reflected the influences of human activities.…”
Section: Sources and Influencing Factors For The Major Ions And Potensupporting
confidence: 65%
“…Because the water samples from the upper reaches of Syr Darya River and its tributaries mainly belong to the calcium bicarbonate category, carbonate dissolution may dominate the hydrochemical composition. If only carbonate dissolution occurs, the values of Ca 2+ /HCO 3 − and (Ca 2+ + mg 2+ )/HCO 3 − will be close to 0.5 [62]. In this area, If the Ca 2+ originates from gypsum dissolution, the ratio of Ca 2+ /SO 4 2− will be nearly equal to 1 [63].…”
Section: Sources and Influencing Factors For The Major Ions And Potenmentioning
confidence: 93%
“…5 ). Due to the proximity of both study sites to its spring, the observed dominance of R rates may also reflect a residual signal from upstream DO-undersaturated spring water that was also measured by van Geldern et al 90 .…”
Section: Discussionmentioning
confidence: 61%
“…Additionally, at the WIS stream elevated nitrate concentrations were derived from the nitrate-rich spring and groundwater input from agriculturally influenced land use. This was combined with reduced nutrient attenuation potential of the karstic bedrock 90 . The elevated nutrient concentrations in combination with reduced shading likely fueled the photosynthetic activity during day time even in the proximity of the spring.…”
Section: Discussionmentioning
confidence: 99%
“…However, in the present study, the Ca 2+ /SO4 2-ratio was much greater than 1 (Figure 9), indicating that the excess Ca 2+ came from the dissolution of carbonate or silicate minerals. When the basin water is mainly affected by carbonate weathering, due to the subsequent chemical weathering process, the (Ca 2+ + Mg 2+ )/HCO3 -equivalent concentration ratio is about 0.5 [37,58]. From the water equivalent For a single ion component, if the Ca 2+ originated from gypsum dissolution, the Ca 2+ /SO 4 2− ratio would be close to 1 [57].…”
Section: Applicability For Irrigation and Human Health Risk Evaluationmentioning
confidence: 99%